Preservice Teachers’ Implicit and Explicit Attitudes Towards Teaching and Learning - Zaruba, Nicole; Westphal, Andrea; Gutmann, Franziska; Vock, Miriam (Frontiers in Education, 2021)
When it comes to teacher attitudes towards teaching and learning, research relies heavily on explicit measures (e.g., questionnaires). These attitudes are generally conceptualized as constructivist and transmissive views on teaching and learning with constructivism often considered to be more desirable. In explicit measures, this can have drawbacks like socially desirable responding. It is for this reason that, in this study, we investigated implicit attitudes as well as explicit attitudes towards constructivism and transmission. N = 100 preservice teachers worked on a questionnaire and two Single-Target Implicit Association Tests (ST-IAT constructivism and ST-IAT transmission) before (T1) and after (T2) a single master’s semester. One group (n = 50) did student teaching while a second group (n = 50) took master’s courses. We evaluated preservice teachers’ views on teaching at the end of their masters’ studies. Participants agreed with transmission and constructivism (T1) on both an explicit and implicit level. Implicit measures seem to exceed explicit measures in differentially assessing constructivist and transmissive views on teaching and learning. After student teaching (T2), there was no overall effect of attitude development but changes in rank indicate that participants’ implicit attitudes towards constructivism and transmission developed differently for each individual.